A Silver (I) Complex-Loaded Lipid Nanoemulsion: A New Approach Against Candida albicans Biofilms - Fortunato, Giovanna Capaldi [UNESP]; Marena, Gabriel Davi; Silva, Débora Eduarda Soares [UNESP]; Ribeiro, Tamara Renata Machado [UNESP]; Moreira, Cristiano Gallina [UNESP]; Nogueira, Flávia Aparecida Resende; Di Filippo, Leonardo Delello [UNESP]; Chorilli, Marlus [UNESP]; Netto, Adelino Vieira de Godoy [UNESP]; Bauab, Taís Maria [UNESP] (MDPI, 2025)
Introduction: The increasing prevalence of fungal infections, particularly those caused by Candida albicans, presents a significant clinical challenge due to the emergence of drug-resistant strains. Silver (I) coordination complexes show promise as antifungal agents; however, their poor water solubility limits clinical application. Methods: In this study, we developed and characterized a lipid nanoemulsion (Ag-LN) to enhance the delivery and activity of a silver (I) complex. Results: The formulation exhibited nanoscale size, spherical morphology, and stability for up to 60 days. Ag-LN showed potent antifungal effects, preventing biofilm formation and eradicating mature biofilms. Importantly, nanoencapsulation preserved antifungal activity while reducing mutagenic potential and acute toxicity compared with the free compound. Conclusions: These findings support Ag-LN as a promising antifungal platform for future preclinical studies.